2023
DOI: 10.1007/s43994-023-00029-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico anti-quorum sensing activities of phytocompounds of Psidium guajava in Salmonella enterica serovar Typhi

Abstract: Biofilm contributes hugely to the persistence of typhoid fever in human population and quorum sensing (QS) is an integral mechanism involved in biofilms. Interruption of the QS network has therefore been put forward as one of the important anti-virulence strategies. Methanol extract of Psidium guajava leaves has been confirmed to possess antibacterial and anti-biofilm activities against Salmonella Typhi. This study therefore aimed at investigating the interactions of phytocompounds previously identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, quercetin can inhibit biofilm production and twitching motility. 57 Olaniyi et al 58 Benzene ethanamine, 4-methoxy- and Cyclopentadecanone, 2-hydroxy- from Psidium guajava leaves showed inhibitory properties against QS proteins of Salmonella Typhi .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quercetin can inhibit biofilm production and twitching motility. 57 Olaniyi et al 58 Benzene ethanamine, 4-methoxy- and Cyclopentadecanone, 2-hydroxy- from Psidium guajava leaves showed inhibitory properties against QS proteins of Salmonella Typhi .…”
Section: Discussionmentioning
confidence: 99%
“…Z-phytol and lonazolac molecules were recognized as candidates for in vitro inhibition. Also, in silico anti-QS activities of Benzeneethanamine, 4-methoxyand 2-Cyclopentadecanone, 2-hydroxy by a SdiA protein interaction were predicted [39]. Phytochemical berberine was studied [40] as an antibiofilm inhibitor using crystal violet microtiter plate assay; berberine showed 31.20% antibiofilm activity at 0.019 mgÁmL À1 in front S. enterica sv Typhimurium and QS inhibitory potential was screened using Chromobacterium violaceum biosensor bacteria.…”
Section: Nanosystems Tested In Vitro and In Silico For Biofilm Inhibi...mentioning
confidence: 99%
“…[18] At the moment, a more stringent P. guajava phytocompounds have proved in-silico antiquorum sensing activities against Salmonella enterica serovar Typhi, and it was suggested that these compounds are more effective than ciprofloxacin, the conventional drug used to treat typhoid fever. [19] The antihyperglycemic, antihyperlipidemic, antiobesity potential and possible use in diabetes-associated disorders like high blood pressure and malfunction of kidney, all have been explored in-vitro investigations of guava leaves and fruits. [20] P.guajava extract treatment improved blood glucose lowering after a glucose load and lessened damage to the pancreatic islets in diabetic animals.…”
Section: Introductionmentioning
confidence: 99%